1999
DOI: 10.1161/01.res.85.8.699
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor Activation Induces Vascular Endothelial Growth Factor in Human Retinal Endothelial Cells

Abstract: Adenosine, released in increased amounts by hypoxic tissues, is thought to be an angiogenic factor that links altered cellular metabolism caused by oxygen deprivation to compensatory angiogenesis. Adenosine interacts with 4 subtypes of G protein-coupled receptors, termed A(1), A(2A), A(2B), and A(3). We investigated whether adenosine causes proliferation of human retinal endothelial cells (HRECs) and synthesis of vascular endothelial growth factor (VEGF) and, if so, which adenosine receptor subtype mediates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 40 publications
5
138
2
1
Order By: Relevance
“…However, it has been described that adenosine A 2A (and A 2B ) receptors may increase endothelial proliferation/migration and in vitro angiogenesis capacity, as well as induce vasodilatation, increase the synthesis of proangiogenic factors (i.e., VEGF), or decrease expression of antiangiogenic factors such as sFLT-1 [see details in 1]. In particular, other [2,4,6] and we [14,36] have previously showed that stimulation of A 2A receptor increased the expression of VEGF in endothelial cells, as confirmed in the current work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been described that adenosine A 2A (and A 2B ) receptors may increase endothelial proliferation/migration and in vitro angiogenesis capacity, as well as induce vasodilatation, increase the synthesis of proangiogenic factors (i.e., VEGF), or decrease expression of antiangiogenic factors such as sFLT-1 [see details in 1]. In particular, other [2,4,6] and we [14,36] have previously showed that stimulation of A 2A receptor increased the expression of VEGF in endothelial cells, as confirmed in the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a nucleoside, which activates a family of Gcoupled protein receptors, named adenosine receptor (AR), type 1 (A 1 ), 2A (A 2A ), 2B (A 2B ), and 3 (A 3 ), and can control expression of pro-angiogenic factors such as vascular endothelial growth factor (VEGF) [1][2][3][4][5][6]. However, depending on the tissue or cell approach, A 2A and A 2B may play a dominant role in regulating pro-angiogenic processes [2,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the A2-type receptors have been described as sensors of tissue damage during an immune response (2), and A2aARs have been described as having a nonredundant role in the attenuation of inflammation and tissue damage in vivo (3). Indirect evidence suggests that the adenylyl cyclase stimulatory A2b adenosine receptors (A2bARs) also affect vascular function (4)(5)(6). For instance, adenosine inhibits the proliferation of murine VSMC via activation of the A2bAR (4).…”
Section: Inflammation ͉ Cxcr4mentioning
confidence: 99%
“…For instance, adenosine inhibits the proliferation of murine VSMC via activation of the A2bAR (4). On the other hand, A2bAR activation induces growth of human vascular endothelial cells and stimulates MAP kinase activity in other cell types (5,6). Additional studies suggest that adenosine induces apoptosis of human arterial smooth muscle cells, which is mediated via the A2bAR in a cAMP-dependent pathway (7).…”
Section: Inflammation ͉ Cxcr4mentioning
confidence: 99%
“…In contrast, when adenosine activates the A 2A receptors, cAMP level increases, which causes airway relaxation (29). Adenosine A 2B receptors have long been known to be coupled to G s protein, which mediates the activation of adenylyl cyclase (12,33). Recent studies indicate that A 2B receptors are also coupled to G q and result in Ca 2ϩ mobilization and mitogen-activated protein kinase activation (20,21).…”
mentioning
confidence: 99%